Teaching research methodology to student midwives through a socio-constructivist educational model: The experience of the high school for science and health techniques of Tunis. (February 2016) - Gherissi, Atf; Tinsa, Francine; Soussi, Sonia; Benzarti, Anis
Abstract: Since its independence in 1956, Tunisia's maternal health indicators have steadily improved as the result of the implementation of a national holistic strategy that emancipated women and developed midwifery education and maternal health services provision. The last review of the midwifery education programme, occurred in 2008, and was based on evidence based core competencies. This paper describes the implementation process of the socio-constructivist educational model used by to teach research methodology to student midwives, the changes observed among them, the challenges and the lessons learned.